Проблемні питання безпеки дорожнього руху в Україні (повідомлення 1) = Topical issues of road-traffic safety in Ukraine (report 1) - T. L. Lebedeva (Kazimierz Wielki University, 2015)
Lebedeva T. L. Проблемні питання безпеки дорожнього руху в Україні (повідомлення 1) = Topical issues of road-traffic safety in Ukraine (report 1). Journal of Education, Health and Sport. 2015;5(6):472-481. ISSN 2391-8306. DOI 10.5281/zenodo.27404 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A472-481 https://pbn.nauka.gov.pl/works/605083 http://dx.doi.org/10.5281/zenodo.27404 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015.   ПРОБЛЕМНІ ПИТАННЯ БЕЗПЕКИ ДОРОЖНЬОГО РУХУ В УКРАЇНІ (ПОВІДОМЛЕННЯ 1) TOPICAL ISSUES OF ROAD-TRAFFIC SAFETY IN UKRAINE (report 1)   Т. Л. Лєбєдєва T. L. Lebedeva   ДП Український НДІ медицини транспорту МОЗ України, м. Одеса State Enterprise "Ukrainian Research Institute for Medicine of Transport", Odessa   Absrtact The analysis of crush rate in Ukrainian traffic road during 1990-2014 has been made. The necessity of  system-wide approach for decrease of accident risk has been substantiated. It has been suggested to estimate accident severity by calculating the number of victims and persons traumatize on 100 accidents with sufferers when analyze crush rate. Keywords: road traffic injuries, statistics, killed, injured.   Резюме Проведено аналіз дорожньо-транспортного травматизму на автошляхах України за 1990-2014 роки. Визначена необхідність системного підходу для зниження аварійності. Запропоновано при аналізі аварійності оцінювати важкість наслідків ДТП за розрахунком кількості загиблих та травмованих на 100 ДТП з постраждалими. Ключові слова: дорожньо-транспортний травматизм, статистика, загиблі, травмовані.   Резюме ПРОБЛЕМНЫЕ ВОПРОСЫ БЕЗОПАСНОСТИ ДОРОЖНОГО ДВИЖЕНИЯ В УКРАИНЕ (СООБЩЕНИЕ 1). Проведен анализ дорожно-транспортного травматизма на автодорогах Украины за 1990-2014 годы. Показана необходимость системного подхода для снижения аварийности. Предложено при анализе аварийности оценивать тяжесть последствий ДТП по расчету количества погибших и травмированных на 100 ДТП с пострадавшими. Ключевые слова: дорожно-транспортный травматизм, статистика, погибшие, травмированные.